The neural basis of belief-attribution across the lifespan: False-belief reasoning and the N400 effect. (May 2020) - Bradford, Elisabeth E.F.; Brunsdon, Victoria E.A.; Ferguson, Heather J.
Abstract: The current study examined how social cognition – specifically, belief-state processing – changes across the lifespan, using a large sample ( N = 309) of participants aged 10–86 years. Participants completed an event-related brain potential study in which they listened to stories involving a character who held either a true- or false-belief about the location of an object, and then acted in a manner consistent or inconsistent to this belief-state. Analysis of the N400 revealed that when the character held a true-belief, inconsistent outcomes led to a more negative-going N400 waveform than consistent outcomes. In contrast, when the character held a false-belief, consistent outcomes led to a more negative-going N400 waveform than inconsistent outcomes, indicating that participants interpreted the character's actions according to their own more complete knowledge of reality. Importantly, this egocentric bias was not modulated by age in an early time window (200–400 msec post-stimulus onset), meaning that initial processing is grounded in reality, irrespective of age. However, this egocentric effect was correlated with age in a later time window (400–600 msec post-stimulus onset), as older adults continued to consider the story events according to their own knowledge of reality, but younger participants had now switched to accommodate the character's perspective. In a final 600–1000 msec time window, this age modulation was no longer present. Interestingly, results suggested that this extended egocentric processing in older adults was not the result of domain-general cognitive declines, as no significant relationship was found with executive functioning (inhibitory control and working memory).